2019
DOI: 10.3349/ymj.2019.60.2.148
|View full text |Cite
|
Sign up to set email alerts
|

MiR-182-5p Knockdown Targeting PTEN Inhibits Cell Proliferation and Invasion of Breast Cancer Cells

Abstract: PurposeBreast cancer (BC) is one of the most common malignant tumors, affecting a significant number of women worldwide. MicroRNAs (miRNAs) have been reported to play important roles in tumorigenesis. The aim of this study was to determine the roles of miR-182-5p in BC progression.Materials and MethodsThe expressions of miR-182-5p and phosphatase and tensin homolog deleted on chromosome 10 (PTEN) were measured in BC tissues and cells by quantitative real-time polymerase chain reaction or Western blot. Cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The reason that miRNAs have been widely studied is that circRNA can function as "miRNA sponges" to regulate downstream gene expression, thus participating in the regulation of cancer progression [17,18]. MiR-182-5p is a widely highly expressed miRNA in many cancers and can promote proliferation and metastasis in cancer cells, such as breast cancer and hepatocellular carcinoma [19,20]. Studies have shown that miR-182-5p is upregulated in OSCC and is related to OSCC metastasis [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The reason that miRNAs have been widely studied is that circRNA can function as "miRNA sponges" to regulate downstream gene expression, thus participating in the regulation of cancer progression [17,18]. MiR-182-5p is a widely highly expressed miRNA in many cancers and can promote proliferation and metastasis in cancer cells, such as breast cancer and hepatocellular carcinoma [19,20]. Studies have shown that miR-182-5p is upregulated in OSCC and is related to OSCC metastasis [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…miR-548 promoted NSCLC cell invasion by regulating PTEN ( 23 ). Moreover, miR-182 promoted breast cancer cell viability and invasion via targeting PTEN ( 24 ). A previous study has shown that miR-494-3p can promote the progression of endometrial cancer by regulating the PTEN/PI3K/AKT pathway ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that glioma-secreted exosomes can be effectively absorbed by endothelial cells. miR-182-5p has been reported to be involved in tumor proliferation (47)(48)(49)(50)(51)(52)(53), invasion (47,49,51), and metastasis (48,(54)(55)(56)(57). However, the role of miR-182-5p in vascular endothelial cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%